Karakterisasi Gelatin Halal dari Kulit Kepala Ikan Lele Dumbo (Clarias gariepinus) sesuai SNI 06-3735-1995 - Putri Hanifa; Syamsi Aini (Lembaga Yasin AlSys, 2025)
The growing demand for environmentally friendly and halal-compliant gelatin in Indonesia necessitates the exploration of alternative sources based on organic waste. One such potential lies in the underutilized waste of the catfish (Clarias gariepinus) head skin. This study aims to synthesize and characterize halal gelatin derived from catfish head skin using asam kandis (Garcinia cowa) as a natural acid solvent through an acid-based extraction method. The extraction process consisted of three main stages: degreasing, demineralization, and extraction at 55°C. An experimental approach was employed to assess the physicochemical parameters of the extracted gelatin. The analysis revealed moisture content of 10.01%, ash content of 0.24%, fat content of 1.07%, pH of 5.60, gelling point of 13°C, melting point of 29°C, and viscosity of 6.0 cP, all of which comply with the Indonesian National Standard (SNI 06-3735-1995) for gelatin quality. FTIR characterization showed distinctive absorption spectra for Amide A (3276–2939 cm⁻¹), Amide I (1630 cm⁻¹), Amide II (1532–1447 cm⁻¹), and Amide III (1241 cm⁻¹), confirming successful collagen conversion into gelatin. In conclusion, catfish head skin presents promising potential as a halal, eco-friendly gelatin source that meets national quality standards.